Analysis of the Validity of Problem-Based Learning Physics Modules to Facilitate Scientific Literacy in High School Student - Nesa Fadila Zulfa; Hufri Hufri; Yenni Darvina; Emiliannur Emiliannur; Hidayati Hidayati; Letmi Dwiridal (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
This research is driven by the students’ scientific literacy has not been well facilitated because the teaching materials used have not optimally supported its development. The purpose of this study is to develop and analyze the validity of the problem-based learning physics module intended to facilitate students’ scientific literacy. This study employed a research and development (R&D) method to develop and validate the module. The validation process was carried out by three physics lectures from the State University of Padang (UNP) and two high school physics teachers. Expert validation was carried out to assess six component: content feasibility, presentation, graphics, language, problem-based learning steps, and scientific literacy. Based on the data analysis, the developed module obtained a Aiken’s V index of 0.89, which falls into the valid category. Therefore, it can be concluded that the problem-based learning physics module developed to facilitate high school students’ scientific literacy is valid and appropriate for use as an innovative teaching material that effectively supports the physics learning process, particularly on the topic of climate change.